FormTracer: a mathematica tracing package using FORM - Cyrol, Anton Konrad; Mitter, Mario; Strodthoff, Nils (Computer physics communications, 2017)
We present FormTracer, a high-performance, general purpose, easy-to-use Mathematica tracing package which uses FORM. It supports arbitrary space and spinor dimensions as well as an arbitrary number of simple compact Lie groups. While keeping the usability of the Mathematica interface, it relies on the efficiency of FORM. An additional performance gain is achieved by a decomposition algorithm that avoids redundant traces in the product tensors spaces. FormTracer supports a wide range of syntaxes which endows it with a high flexibility. Mathematica notebooks that automatically install the package and guide the user through performing standard traces in space-time, spinor and gauge-group spaces are provided. Program summary Program Title: FormTracer Program Files doi: http://dx.doi.org/10.17632/7rd29h4p3m.1 Licensing provisions: GPLv3 Programming language: Mathematica and FORM Nature of problem: Efficiently compute traces of large expressions Solution method: The expression to be traced is decomposed into its subspaces by a recursive Mathematica expansion algorithm. The result is subsequently translated to a FORM script that takes the traces. After FORM is executed, the final result is either imported into Mathematica or exported as optimized C/C++/Fortran code.